Up-conversion routines of Er3+-Yb3+ doped Y6O5F8 and YOF phosphors - Park, Sangmoon; Yang, Wonseok; Park, Chu-Young; Noh, Minhee; Choi, Seulki; Park, Dahye; Jang, Ho Seong; Cho, So-Hye (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Optical materials composed of a Y6(1-p-q)Er6pYb6qO5F8 (p = 0.001-0.1, q = 0.005-0.1)solid solution with Y0.99Er0.01OF were prepared via a solid-state reaction using excess NH4F flux at 950 degrees C for 30 min. X-ray diffraction patterns of Y6(1-p-q)Er6pYb6qO5F8 and Y0.66Er0.01OF were compared upon altering the synthesis temperature and the molar ratio of the NH4F flux to the Y3+ (Er3+, Yb3+) ions. The effective spectral-conversion properties of Er3+ and Er3+-Yb3+ ions in Y6O5F8 phosphors were monitored during excitation with a 980 nm wavelength diode-laser. Selection of appropriate Er3+ and/or Yb3+ concentrations in the Y6O5F8 structure led to achievement of the desired up-conversion emission, from the green to the red regions of the spectra. Furthermore, the mechanism of up-conversion in the phosphors was described by an energy-level schematic. Up-conversion emission spectra and the dependence of the emission intensity on pump power (between 193 and 310 mW) in the Y6(0.995-q)Er0.03Yb6qO5F8 phosphors were also investigated. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: OXYFLUORIDE; EMISSION; LASER; ER3+